Relationship Between Working Memory and Number Knowledge Skills of Preschool Children - Altan, Rukiyye Yıldız (My University, 2026)
Understanding the factors that influence children’s early mathematics learning is important. This is because these early abilities are strongly linked to later mathematical achievement. The study of the effects of working memory on mathematical achievement has become an area of research that has attracted significant attention in recent years. In this study, the relationships between working memory and number knowledge skills of preschool children were examined. The study was conducted with 165 children (49% girls and 51% boys) enrolled in different kindergartens in the center of Ankara. Working Memory Scale and Updated Early Arithmetic Test were used to collect the data. Pearson Product Moment Correlation Coefficient Analysis and Multiple Linear Regression Analysis were used to analyze the data. The results of the study showed that number knowledge had positive and moderately significant relationships with all sub-variables of working memory. The order of importance of working memory variables on number knowledge is verbal working memory, visual working memory, verbal short-term memory and visual short-term memory. Working memory variables predicting number knowledge explain 55% of the change in number knowledge. The results of the study provide important insights into how practitioners can make adjustments to learning processes to develop working memory capacity in order to teach children number sense skills.
Keywords: Eğitim; Eğitim Araştırmaları; Psikoloji